2019
DOI: 10.1002/ejic.201900133
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen Activation and Functionalization Using β‐Diketiminate Iron Complexes

Abstract: Iron catalysts are adept at breaking the N-N bond of N 2 , as exemplified by the iron-catalyzed Haber-Bosch process and the iron-containing clusters at the active sites of nitrogenase enzymes. This Minireview summarizes recent work that has identified a well-characterized set of multiiron complexes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Nitrogen, like ethylene, also has a molecular weight of 28 Da, and is present in abundance during the ESI-MS experiment thanks to its use as a desolvation gas, and was a possible explanation for this ion. While many dinitrogen complexes have been reported for metal centers in Groups 3-9, some simple, [267][268][269][270][271] some with carefully constructed coordination environments, [272][273][274][275][276][277][278][279][280] and others evolved for nitrogen fixation, [281][282][283][284][285] such complexes are less common in Groups 10 and 11. Isolated dinitrogen complexes involving platinum are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen, like ethylene, also has a molecular weight of 28 Da, and is present in abundance during the ESI-MS experiment thanks to its use as a desolvation gas, and was a possible explanation for this ion. While many dinitrogen complexes have been reported for metal centers in Groups 3-9, some simple, [267][268][269][270][271] some with carefully constructed coordination environments, [272][273][274][275][276][277][278][279][280] and others evolved for nitrogen fixation, [281][282][283][284][285] such complexes are less common in Groups 10 and 11. Isolated dinitrogen complexes involving platinum are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Laplaza and Cummins first found the direct cleavage of dinitrogen in ad initrogen-bridged dimolybdenumc omplexb earing triamide ligands that afforded the corresponding molybdenum-nitride complex. [11] After that foundationalw ork, several studies have explored the direct cleavageo fb ridging dinitrogen species to form the correspondingn itride complexes mediated by other transition metal complexes, [12,13] with the furthert ransformation of the produced nitride complexesu sed as novel methodst os toichiometrically functionalize dinitrogen under mild reaction conditions. [14] The Schrock and MØzailles research groups have reported the formation of molybdenumnitride complexes via direct cleavage of dinitrogenfrom the reductiono fm olybdenum(III) halide complexes bearing similar pincer ligandsu nder atmospheric pressure of dinitrogen gas althoughn od initrogen-bridged dimolybdenumc omplexes were observed as key reactive intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…These values (Extended Data Table 3) are close to the expected charges of  1 and  2 for the TCNQ and (TCNQ-TCNQ) dimers, respectively. The central C=C bond length of the TTF core is 1.323 Å (Extended Data Table 2), suggesting that the TTF moiety is in a neutral state 31 . The scarcity of other supplementary charged species in the crystal channel confirmed the distribution of the valences in the asymmetric unit.…”
Section: Structural Analysis Of Njuz-1 Single Crystalsmentioning
confidence: 99%
“…Compared with the S0 state, the hydrogenation step in the S1 excited state is thermodynamically more favourable, which is an exothermic process. Then, three possible reaction pathways, including the alternating (blue), distal (grey) and mixed (green) pathways 31,32 , are displayed in Extended Data Fig. 7bc.…”
mentioning
confidence: 99%